Increased TIGIT expression correlates with impaired NK cell function in diffuse large B-cell lymphoma - Lu, Hui; Zhao, Xiaoyan; Liu, Liqiong; Zhang, Lu; Wang, Huafang (Frontiers in Oncology, 2025)
PurposeThis study aims to investigate the status of natural killer (NK) cells and the role of T-cell immunoreceptor with Ig and ITIM domains (TIGIT)-mediated regulation in diffuse large B-cell lymphoma (DLBCL).MethodsPeripheral blood samples from 30 newly diagnosed DLBCL patients and 25 healthy controls were collected. Multiparametric flow cytometry was used to analyze the expression levels of TIGIT and its family molecules (CD226 and CD96) on NK cells, as well as to assess NK cell phenotype and function. The restorative effects of TIGIT blockade on NK cell cytotoxicity were evaluated through in vitro functional assays and in vivo animal models.ResultsCompared to healthy controls, DLBCL patients exhibited significantly reduced percentages and absolute numbers of NK cells. TIGIT expression was markedly upregulated on NK cells in DLBCL patients, while CD226 expression was downregulated; however, no significant difference in CD96 expression was observed. These alterations were associated with impaired NK cell function in DLBCL patients, including reduced secretion of activation factors such as granzyme B, perforin, and CD107a. Importantly, TIGIT blockade significantly enhanced the cytotoxic activity of NK cells against DLBCL cells in both in vitro and in vivo settings.ConclusionDysregulated expression of TIGIT and its family molecules on NK cells contributes to NK cell dysfunction and promotes tumor immune escape in DLBCL. These findings highlight TIGIT as a promising therapeutic target for restoring NK cell-mediated antitumor immunity in DLBCL.